2014
DOI: 10.3389/fchem.2014.00094
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis and structural characterization of ammonium ion-templated lanthanide(III) carboxylate-phosphonates

Abstract: Using N-(phosphonomethyl) iminodiacetic acid (H4PMIDA), as a complexing agent, two new complexes, (NH4)La(PMIDA)(H2O)•H2O, 1 and (NH4)Yb(PMIDA), 2 have been synthesized hydrothermally. In both compounds, the metal ions are trapped by a three five-membered chelate rings by the chelating PMIDA anions giving a tricapped trigonal prismatic LaO8N and monocapped trigonal prismatic YbO6N geometries for 1 and 2, respectively. The structure of 1 consists of La(PMIDA)(H2O) chelating units, linked together by the phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The study revealed stronger toxicity of two metabolites such as PMIDA and bis-(phosphonomethyl)amine, which may be associated with complexation of metal divalent ions by these substances. Aiy et al [ 31 ] showed that these compounds can bind divalent ions, including calcium. This phenomenon could explain a decrease in the ATP level observed in our study, which could have been linked with alterations in calcium ion level in this organellum.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed stronger toxicity of two metabolites such as PMIDA and bis-(phosphonomethyl)amine, which may be associated with complexation of metal divalent ions by these substances. Aiy et al [ 31 ] showed that these compounds can bind divalent ions, including calcium. This phenomenon could explain a decrease in the ATP level observed in our study, which could have been linked with alterations in calcium ion level in this organellum.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the reported crystal structures of the RE complexes of the aminophosphonic acids, with varying coordination numbers from six to nine, in most of which no N-RE bond has been detected [ 69 , 70 , 71 , 72 , 73 ]. There are few crystal structures where nitrogen is coordinated to RE, but typically, these α-aminophosphonates had either multiple nitrogen atoms coordinate to RE [ 74 , 75 , 76 ] or the coordination was dictated by carboxylic acid groups due to the oxophilic nature of REs [ 77 , 78 ].…”
Section: Characterization Of the Extracted Metal Complexes By Irmentioning
confidence: 99%